Nutritional value of black and white oat cultivars ensiled in two phenological stages - David,Diego Bitencourt de (2010)
It was evaluated in this work, crop yield, fermentative quality and nutritional value of the silage of cultivars of white (Avena Sativa L.) and black (Avena Strigosa Schreb) oats cut at two development stages. It was used an experimental randomized block design in a 4 x 2 factorial scheme, consisting of four oat cultivars (two cultivars of black oats: Aveia Preta Comum and UTFP 971; and two cultivars of white oats: ER 91156- 1- 2- 1 and SI 98105- b), with four replicates. The cultivars were ensiled at flowering and dough grain stages. Oat cut at dough grain stage, especially genotypes from white oat, allows the obtainment of a more productive and qualitative silage. Cultivar, genotype, and maturation stage affect protein fractioning and oat silage carbohydrates.